2014
DOI: 10.1155/2014/703806
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Studies on High-Velocity Oxy-Fuel Spraying of CoNiCrAlY Coatings Used in the Aeronautical Industry

Abstract: The thermal spraying process is a surface treatment which does not adversely affect the base metal on which it is performed. The coatings obtained by HVOF thermal spray are employed in aeronautics, aerospace, and power generation industries. Alloys and coatings designed to resist oxidizing environments at high temperatures should be able to develop a surface oxide layer, which is thermodynamically stable, slowly growing, and adherent. MCrAlY type (M = Co, Ni or combination of both) coatings are used in wear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 7 publications
3
21
0
Order By: Relevance
“…the higher coating roughness after spraying in comparison to the roughness value of the ground surface of the reference sample. The obtained values of coefficient of friction for coatings after spraying are comparable to the values presented in the work of Cabral-Miramontes et al [20] measured for coatings of the MCrAlY type sprayed with the HVOF method at different process parameters (torch-substrate distance).…”
Section: Results Of Wear Resistance Testssupporting
confidence: 88%
“…the higher coating roughness after spraying in comparison to the roughness value of the ground surface of the reference sample. The obtained values of coefficient of friction for coatings after spraying are comparable to the values presented in the work of Cabral-Miramontes et al [20] measured for coatings of the MCrAlY type sprayed with the HVOF method at different process parameters (torch-substrate distance).…”
Section: Results Of Wear Resistance Testssupporting
confidence: 88%
“…This is in agreement with the data reported in the literature [14,19]. The hardness ranges from 4.7 to 5.8 GPa, which is comparable with the literature data [19,33]. Table 2.…”
Section: Coating Characterizationsupporting
confidence: 92%
“…Pure MCrAlYs, however, are unsuitable for tribological applications, because their low hardness would result in very severe wear under sliding contact conditions, particularly during running-in stages at low temperatures. Literature studies on this topic have indeed reported significant wear by adhesion and delamination mechanisms under rotating and oscillating sliding [8][9][10].…”
Section: Introductionmentioning
confidence: 94%